Kajian Hukum Penanganan Tindak Pidana Kecelakaan Lalu Lintas Dengan Pola Manajemen Kepolisian Berdasarkan Undang-Undang RI Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Emi Sri Utami (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2016)
Traffic problems are problems that cause a lot of problems, because it concerns the problem of order and security in society. According Polrestabes Bandung and Jasa Marga of the results of research in the field shows the rate of accidents in the city and throughout Indonesia is quite high. Based on the above, the authors feel compelled to do more research and then examines the problems that subsequently the authors formulate it in the form of a thesis with the title: